What is Interdisciplinary about Victorian History today? - Rohan McWilliam (19, 2005)
This article examines the way demands for interdisciplinarity have shaped the writing of Victorian history in recent years. It briefly explores the writing of Victorian history since the 1930s (arguing that the interdisciplinary impulse is nothing new) so as to consider the peculiarities of the post-1980 historiography. A range of works by cultural historians (such as Judith Walkowitz and Peter Bailey) who made a distinctive contribution to debates about the Victorians in the late twentieth century are assessed in order to understand the current state of the academic conversation. The article discusses both the strengths and weaknesses of recent approaches. It argues that interdisciplinary cultural history has so far resisted attempts to create a new synthesis and ponders ways in which such a synthesis might be achieved.